2000
DOI: 10.1523/jneurosci.20-06-02218.2000
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and Differentiation of Progenitor Cells Throughout the Intact Adult Rat Spinal Cord

Abstract: The existence of multipotent progenitor populations in the adult forebrain has been widely studied. To extend this knowledge to the adult spinal cord we have examined the proliferation, distribution, and phenotypic fate of dividing cells in the adult rat spinal cord. Bromodeoxyuridine (BrdU) was used to label dividing cells in 13- to 14-week-old, intact Fischer rats. Single daily injections of BrdU were administered over a 12 d period. Animals were killed either 1 d or 4 weeks after the last injection of BrdU.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
582
4
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 713 publications
(632 citation statements)
references
References 50 publications
43
582
4
3
Order By: Relevance
“…Multi-potential precursors are abundant in many regions of the adult brain parenchyma [31][32][33][34]. In particular, oligodendrocyte progenitor cells (OPCs) were isolated from various regions of the adult rodent CNS [35][36][37], and were identified also in the adult human brain [38][39][40][41][42] and spinal cord [43]. OPCs are identified by expression of chondroitin-sulfate proteoglycan NG2+ and of platelet-derived growth factor receptor-α are highly abundant in the adult CNS, comprising up to 5% of its cells [37].…”
Section: Glial Progenitor Cells In the Adult Central Nervous Systemmentioning
confidence: 99%
“…Multi-potential precursors are abundant in many regions of the adult brain parenchyma [31][32][33][34]. In particular, oligodendrocyte progenitor cells (OPCs) were isolated from various regions of the adult rodent CNS [35][36][37], and were identified also in the adult human brain [38][39][40][41][42] and spinal cord [43]. OPCs are identified by expression of chondroitin-sulfate proteoglycan NG2+ and of platelet-derived growth factor receptor-α are highly abundant in the adult CNS, comprising up to 5% of its cells [37].…”
Section: Glial Progenitor Cells In the Adult Central Nervous Systemmentioning
confidence: 99%
“…Fortunately, antibodies are available to recognize BrdU by immunohistochemistry. Microglia are rarely dividing in the intact spinal cord (Horner et al, 2000). However, microglia proliferation occurs after nerve injury (Graeber et al, 1988) and was found in diverse models of neuropathic pain.…”
Section: Microglia Activation and Proliferation In The Spinal Cord Inmentioning
confidence: 99%
“…Stem/progenitor cells have been iden- (4,14,17,25,29,30,42,44) or intrathecal administration of mitogenic growth factors (16,19). In lower vertebrates, tified in the adult rat and mouse spinal cord (14,15,17,24,(28)(29)(30)36,46,47). In response to injury, these cells ependymal cells rapidly proliferate, migrate, and differentiate to regenerate the adult spinal cord (9,31,37).…”
Section: Introductionmentioning
confidence: 99%